Pengembangan Modul Ajar Materi Puisi dengan Pendekatan Kontekstual pada Kurikulum Merdeka untuk Siswa Kelas X SMKN 1 Percut Sei Tuan Tahun Pembelajaran 2022/2023 - Ellen Cyndi Hutahean; Oky Fardian Gafari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research focuses on developing a teaching module for poetry material with a contextual approach in the Independent Curriculum for class X students at SMK N 1 Percut Sei Tuan for the 2022/2023 academic year. The results of the author's interviews with several students at SMKN 1 Percut Sei Tuan show that students lack confidence in learning to write poetry, and students are even less interested in poetry material. This is proven by the level of student learning focus, namely only 40% of all students are focused during the teaching and learning process. Apart from that, the lack of references for vocabulary and ideas that will be expressed when learning to write poetry is also one of the obstacles experienced by students. The researcher took research samples from three classes, namely TKJ 1 with 32 students, TKJ 2 with 32 students, and TKJ 3 with 32 students, so the total sample was 96 people. The type of research carried out in this research uses the research and development (RnD) method. The validation results from material experts and design experts on the teaching materials developed show the